Oral bleeding in dengue fever - Our perspective (Bangladesh Journal of Medical Science, 2021)
Dengue fever is one of the major public health problem in the tropical and subtropical countriesacross the globe with around 50-100 million cases occurring annually. It is a mosquito bornedisease caused by dengue virus of Flaviviridae family. There are four known serotypes ofdengue virus found worldwide. Aedesaegypti mosquito is the principal vector of transfer ofdengue virus in humans. Dengue clinically presents with high grade fever, chills, head-ache,retro orbital and severe back ache and sometimes with hemorrhagic manifestations whichcan occur without plasma leakage and also with plasma leakage as dengue hemorrhagic fever(DHF) and Dengue shock syndrome (DSS). Oral bleeding is one of the important hemorrhagicmanifestations of dengue clinically manifesting as petechiaes, ecchymosis, gingival bleedingand hematomas .The dentist is sometimes the first person who encounters these types of cases.Therefore, timely diagnosis and prompt referral can prevent morbidity and mortality. This paperdiscusses about the clinical and diagnostic perspectives which a dentist should know in order todiagnose a case of dengue fever presenting with oral bleeding.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.11-16